We are asked to transform the given equation into slope intercept form. The given expression is 2-3y+6x=0. To do this, we need to remember the slope-intercept form is below: y = mx + b where "m" represents the slope and "b" represents the y-intercept The solution of the problem is shown below: 2 - 3y + 6x = 0 ,transpose -3y to the opposite side such as: 2 + 6x = 3y , re-arranging the given we have: 3y = 6x + 2 , divide both sides by 3 such as: 3y/3 = (6x +2) / 3 y = 2x + 2/3 where m = 2 and b = 2/3 The answer is y = 2x + 2/3.
Which of the following equations is the equation 2 - 3y + 6x = 0 written in slope-intercept form? y = -2x - 2/3 y = (1/2)x + 2 y = 2x + 2/3